Enhancing Skills, Effecting Change: Evaluating an Intervention for Students with Below-proficient Information Literacy Skills - Latham, Don; Gross, Melissa (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
An intervention was developed for first-year community college students with below proficient information literacy skills. This presentation focuses on the development of the intervention and the evaluation of the intervention through pre- and post-intervention surveys, and in-depth interviews with intervention participants. A été conçue une séance d’intervention s’adressant aux étudiants de première année d’un collège communautaire ayant des lacunes en maîtrise de l’information. Cette communication porte sur le développement et l’évaluation de cette intervention au moyen de questionnaires pré et post intervention et d’entrevues en profondeur avec les participants. ***Full paper in the Canadian Journal of Information and Library Science***